Goddesses - Manimekalai, Leena (Kanavuppattarai, 2007)
Verzio FF Submission “Goddesses” is the story of three ordinary women from Tamil Nadu, India. They are prematurely aged and dirty. They live and work according to the rules they have set for themselves. Lakshmi, a professional 'funeral singer' visits bereaved houses with a troupe of drummers and for a pittance, she wails and laments and shares the grief of the other mourners. Krishnaveni, the ‘grave-digger’ earns her daily meal by accepting unclaimed bodies from the local police in order to give them a decent burial or cremation, digging and maintaining the graves herself. Sethuraku, the ‘fisherwoman’ goes out to sea, every morning with a few fellow fisherwomen to collect fish and prawns, singing to welcome the day. A story of women who are single but brave and who live extraordinary lives, surviving the darkest of times by going against society's norms.